1994
DOI: 10.1083/jcb.125.6.1371
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of cell adhesion and microvilli formation by antisense oligonucleotides to ERM family members.

Abstract: Abstract. To examine the functions of ERM family members (ezrin, radixin, and moesin), mouse epithelial cells (MTD-1A cells) and thymoma cells (L5178Y), which coexpress all of them, were cultured in the presence of antisense phosphorothioate oligonucleotides (PONs) complementary to ERM sequences. Immunoblotting revealed that the antisense PONs selectively suppressed the expression of each member. Immunofluorescence microscopy of these ezrin, radixin, or moesin "single-suppressed" MTD-1A cells revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
280
1
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(300 citation statements)
references
References 34 publications
15
280
1
2
Order By: Relevance
“…ERM proteins control cell shape primarily by regulating membrane protrusions and cell-substrate adhesion. In epithelial cells ERM proteins are necessary for the formation of apical microvilli (12)(13)(14). In fibroblasts ERM proteins regulate the assembly of focal adhesions (15) and dynamic membrane protrusions, including filopodia and lamellipodia (16,17).…”
mentioning
confidence: 99%
“…ERM proteins control cell shape primarily by regulating membrane protrusions and cell-substrate adhesion. In epithelial cells ERM proteins are necessary for the formation of apical microvilli (12)(13)(14). In fibroblasts ERM proteins regulate the assembly of focal adhesions (15) and dynamic membrane protrusions, including filopodia and lamellipodia (16,17).…”
mentioning
confidence: 99%
“…ERM proteins are localized at the plasma membrane in actin-rich surface structures (Fig 1) [5], such as microvilli, membrane ruffles, and lamellipodia in gut cells, lymphocytes, hepatocytes, spermatozoids, fibroblasts and in a variety of other cell types [5][6][7][8][9]. They are involved in various physiological processes including establishment of cell polarity, cell motility and cell signaling [10].…”
Section: General Overview Of Erm Proteins (Ezrin Radixin Moesin)mentioning
confidence: 99%
“…The suppression of ERM expression by antisense oligonucleotides in thymoma cells as well as in mouse epithelial cells leads to the destruction of both cell-cell and cell-substrate adhesion [22] . Overexpression of ezrin in insect cells enhances cell adhesion [24] .…”
Section: Cell-substrate and Cell-cell Adhesionmentioning
confidence: 99%
“…More recently, several functional analyses demonstrated that they are involved in membrane structures formation. When thymoma cells are cultured in presence of antisense oligonucleotides, which suppress the expression of the three ERM, microvilli disappear from the cell surface [22] . A treatment of primary retinal pigment epithelium (PRE) culture with ezrin antisense oligonucleotides caused complete disappearance of apical microvilli [23] .…”
Section: Erm: Functional Insight: 81 Formation Of Cell Surfacementioning
confidence: 99%